Fingerroot, Boesenbergia rotunda and its Aphrodisiac Activity - Ongwisespaiboon, Oranun; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Boesenbergia rotunda (Family: Zingiberaceae) as known as fingerroot is a daily food ingredient and traditional medicinal plant in Southeast Asia and Indo‑China. It has been shown to possess anti‑allergic, antibacterial, anticancer, anti‑inflammatory, antioxidant, and antiulcer activities and also shown wound healing. Its common phytochemical components include alkaloids, essential oils, flavonoids, and phenolics. This plant is rich in boesenbergin, krachaizin, panduratin, and pinostrobin, all of which has been reported to contribute to its remedial properties including aphrodisiac property. Based on established literature on the aphrodisiac property of B. rotunda and possible mode of action, this review article has attempted to compile that B. rotunda could be further explored for the development of potential aphrodisiac treatment.
Keywords: Aphrodisiac; Boesenbergia rotunda; plant; sex behavior; traditional medicine